Transcriptomic Identification of Draxin-Responsive Targets During Cranial Neural Crest EMT - Hutchins, Erica J.; Piacentino, Michael L.; Bronner, Marianne E. (Frontiers in Physiology, 2021)
Canonical Wnt signaling plays an essential role in proper craniofacial morphogenesis, at least partially due to regulation of various aspects of cranial neural crest development. In an effort to gain insight into the etiology of craniofacial abnormalities resulting from Wnt signaling and/or cranial neural crest dysfunction, we sought to identify Wnt-responsive targets during chick cranial neural crest development. To this end, we leveraged overexpression of a canonical Wnt antagonist, Draxin, in conjunction with RNA-sequencing of cranial neural crest cells that have just activated their epithelial—mesenchymal transition (EMT) program. Through differential expression analysis, gene list functional annotation, hybridization chain reaction, and quantitative reverse transcription polymerase chain reaction (RT-qPCR), we validated a novel downstream target of canonical Wnt signaling in cranial neural crest—RHOB—and identified possible signaling pathway crosstalk underlying cranial neural crest migration. The results reveal novel putative targets of canonical Wnt signaling during cranial neural crest EMT and highlight important intersections across signaling pathways involved in craniofacial development.